Reduplication in standard Malay and Japanese - Fujimura Yuko (Journal of Modern Languages)
The Japanese reduplication system has been explained, both at the morphological and semantic levels in contrast to the Malay reduplication system. The above analysis indicates that Malay and Japanese reduplications share some morphological patterns when systematically contrasted.